A Systematic Literature Review: Implementation of Geogebra Mathematical Software on Students Mathematical Abilities in Learning Mathematics - Pinto, Amelia Ancella; Nurhasanah, Farida; Usodo, Budi (KnE Social Sciences, 2025)
Difficulties in learning and mastering mathematics are well-founded, partly because mathematics is a lesson that requires students to think logically, systematically, and reflectively, and requires diligent, thorough, and earnest effort. One way that students can use to hone and improve their mathematical abilities is by applying mathematical software in learning mathematics. One of the widely used mathematical software is Geogebra. This systematic literature review aims to provide a description by analyzing the implementation of Geogebra on students’ mathematical abilities in learning mathematics through literature review. Data collection were carried out by documenting and reviewing 25 articles related to the use of Geogebra on mathematical abilities published in the 2019-2022 period published in national and international journals that can be accessed and downloaded from Google Scholar, ProQuest and Eric databases. Mathematical abilities that can be improved through the application of geogebra include: mathematical communication, understanding of mathematical concepts, mathematical reasoning, solving mathematical problems, and mathematical connections. The results of the study provide information that Geogebra has a positive, effective, and better influence in improving students’ mathematical abilities in the process of learning mathematics. The Geogebra application is also integrated with various models, approaches.